2019
DOI: 10.14744/anatoljcardiol.2019.47381
|View full text |Cite
|
Sign up to set email alerts
|

The better substitute for tricuspid valve replacement in patients with severe isolated tricuspid regurgitation

Abstract: The better substitute for tricuspid valve replacement in patients with severe isolated tricuspid regurgitation Introduction Primary tricuspid valve regurgitation is rarely observed in adults and is known to result from congenital heart disease, rheumatic heart disease, myxomatous valve disease, infective endocarditis, carcinoid syndrome, and/or infiltrative valvulopathy (1). Tricuspid valve repair is the first option for patients with primary or secondary tricuspid regurgitation. However, valve replacement, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Most of the published data found no difference in survival in patients who received mechanical versus bioprosthetic valves, 23) and few studies reported better survival in patients with mechanical 24 , 25) or tissue valves. 8) We did not report a significant difference in survival in patients with mechanical versus tissue valves.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Most of the published data found no difference in survival in patients who received mechanical versus bioprosthetic valves, 23) and few studies reported better survival in patients with mechanical 24 , 25) or tissue valves. 8) We did not report a significant difference in survival in patients with mechanical versus tissue valves.…”
Section: Discussionmentioning
confidence: 67%
“… 7) The reported mortality was as low as 3% in other reports. 8) The wide variability in mortality across the literature could be attributed to the different inclusion criteria and patients’ characteristics. In our study, we included all patients with isolated or combined TVR and those who had primary and reoperative surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The latest studies published seem to agree that mid- and long-term follow-up of biological and mechanical prostheses do not differ in patients undergoing TVR. [ 13 14 ] This is confirmed by a large metanalysis that analyzed more than 2600 patients,[ 15 ] where was observed a higher risk of thrombosis in the case of mechanical TVR. This seems to endorse our philosophy of choosing a bioprosthetic valve in most of our TVR cases.…”
Section: Discussionmentioning
confidence: 81%
“…Based on our search terms and search strategies, the search results were shown in Figure 1 in line with the PRISMA flow chart. (Figure 1) A total of 13 studies [Songur 2014;Liang 2019;Wiedemann 2018;Redondo Palacios 2017;Hwang 2016;Mao 2016;Connolly 2015;Hwang 2014;Rodríguez-Capitán 2013;Cho 2013;Altaani 2013;Garatti 2012;Hwang 2012] with 1453 patients were analyzed, of which 793 patients received biological prostheses, while 660 patients received mechanical prostheses. Individual characteristics of the studies can be seen in Table 1.…”
Section: Resultsmentioning
confidence: 99%